POLA INTERAKSI TINGKAH LAKU INDUK AYAM BETINA DAN ANAK AYAM (Gallus gallus-domesticus) - Anwari Adi Nugroho; Dewi Septiana; Siti Lestari; Demo Rifwan Sugiyarto (Fakultas Sains dan Teknologi Universitas Islam Negeri Alauddin Makassar, 2020)
The purpose of this study was to determine the behavior patterns of female hens and chicks (Gallus gallus-domesticus) in the natural environment. This type of research is descriptive exportative observing patterns of interaction between hens and chicks for 3 days in the morning, afternoon and evening. The study uses ad libitum sampling method. The tools used in the form of cameras and stationery while the materials needed are female hens and 3 chicks. Data was collected by means of observation using observation sheets and documentation tools. Data analysis using descriptive analysis techniques that describe the behavior patterns between the hen with the chick that appears during observation. the results of the study show what the behavior of the mother chickens and their offspring were interacting with. The most common behavior was to look for food, eat and drink, pay attention from the mother to the chicks, and ask for attention from the child to the mother hen. A step that was rarely seen was fighting, avoiding and sleeping.